MASS COMMUNICATION EDUCATION FOR RADIO MOSQUE MANAGERS IN DATING HOAX AND RADICALISM NEWS - Muhammad In'am Esha; R. Taufiqurrochman; Dewi Nur Suci (Abjadia, 2019)
The news hoax and radical understand like a chain that is not separated. Both are very dangerous and have the potential to damage the unity and integrity of the nation and state. This concern encourages researchers to conduct research and assistance for mosque media managers. The sample in this study was the manager of Radio el-Jannah 100.9 FM Malang. This research uses a qualitative approach with four stages: data collection, training, assistance and evaluation. The results of this study indicate that the function of the mosque remains as a center for community empowerment so that it needs to have communication media, one of which is radio which still has a loyal audience segment. The manager of the mosque radio must master the skills of mass communication so that the message broadcast can be well received by the viewers, because from the results of this study it was found that the manager of the mosque's radio had never learned about mass communication. Message and radio broadcast material must be valid, selected, and aimed at educating the public to ward off hoax news and radical understanding.